On Being a Knowledge Angel - Hague, Douglas (Senate Hall, 2004)
This article gives an unashamedly autobiographical view of entrepreneurs, knowledge angels and the relationships between them, being based on the author's direct experience of five start-up companies. It first distinguishes knowledge angels from venture capitalists and business angels, defining knowledge angels as business angels with little capital. Its core is tailor-made case histories of the author and of two young entrepreneurs on whose boards he has worked. This makes it possible to consider the attributes of the author as a knowledge angel and also to identify key characteristics of successful graduate entrepreneurs, including the need for appropriate flexibility; for colleagues who provide a stabilising influence; and for continuous learning from experience and observation. The paper then considers what entrepreneurs seek from knowledge angels - especially experience, expertise and contacts - and what angels obtain for themselves. Finally, there are suggested approaches for future studies in this field. From this article, students and teachers with little business experience will obtain a better understanding of the way that entrepreneurial companies operate, their key business issues and personal relationships within them. It gives readers outside the UK a rare opportunity to identify similarities and differences between start-ups in the UK and in their own countries.
Keywords: knowledge angels|entrepreneurial case histories|support networks